Prevalence, awareness, treatment and control of diabetes in Portugal: Results from the first National Health examination Survey (INSEF 2015). (June 2018) - Barreto, Marta; Kislaya, Irina; Gaio, Vânia; Rodrigues, Ana Paula; Santos, Ana João; Namorado, Sónia; Antunes, Liliana; Gil, Ana Paula; Boavida, José Manuel; Ribeiro, Rogério Tavares; Silva, Ana Clara; Vargas, Patrícia; et al.
Abstract: Aims: Diabetes Mellitus is a major public health threat worldwide and continues to increase in numbers and significance. Estimates of diabetes prevalence, awareness, treatment and control are essential to effectively monitor its trends, plan and evaluate interventions. Methods: We conducted a nationwide health examination survey in the population residing in Portugal aged between 25 and 74 years old in 2015. It consisted in a cross sectional prevalence study which included the measurement of HbA1c, a physical examination and a general health interview of a probabilistic sample of 4911 individuals (Authorization n°9348/2010 of the National Committee for Data Protection). Results: The overall prevalence of diabetes was 9.9% (95%CI: 8.4; 11.5). It was higher in males than in females (12.1% vs 7.8%). Diabetes was more prevalent among individuals of lower education and without any professional activity. The majority of persons with diabetes was aware of their condition (87.1%) and was taking antidiabetic medication (79.7%). Of these, 63.2% had glycated hemoglobin levels lower than 7.0% (53 mmol/mol), but the majority failed to comply with the LDL and blood pressure recommended clinical targets (71.9% and 59.0%). Similarly, the prevalence of prediabetes was 16%, higher among women than men (17.5% vs 14.4%). Conclusion: The prevalence of diabetes and prediabetes remains higher than the global and European estimates, although there is increasing awareness of this disorder.